TROP2 expression as prognostic marker for gastric carcinoma. Issue 2 (17th October 2008) - Mühlmann, G; Spizzo, G; Gostner, J; Zitt, M; Maier, H; Moser, P; Gastl, G; Zitt, M; Müller, H M; Margreiter, R; Öfner, D; Fong, D
Abstract : Background: In gastric cancer the recurrence rate is unacceptably high, even after R0 resection and (neo)adjuvant chemotherapy. Therefore, there is an urgent need for identification of predictive and/or prognostic biomarkers to select high-risk patients who might benefit from additional therapies. Expression of TROP2 has been shown to be associated with tumour aggressiveness and poor prognosis in patients with various epithelial cancers. Aims: To investigate TROP2 expression in gastric cancer and its correlation with clinicopathological features and disease outcome. Methods: Expression of TROP2 was investigated by immunohistochemistry of tumour specimens from 104 patients who underwent resection for gastric cancer. Parameters found to be of prognostic significance in univariate analysis were verified in a multivariate Cox regression model. Results: TROP2 was found to be overexpressed in 58 (56%) tumour samples. Significantly higher expression of TROP2 could be detected in intestinal-type carcinomas (p = 0.03). In intestinal-type gastric cancer, TROP2 overexpression was significantly correlated with shorter disease-free survival (DFS) (p = 0.03). Among the total group, TROP2 overexpression was predictive for poor disease-free (p<0.01) and overall (p = 0.03) survival in lymph node positive patients. Multivariate Cox regression analysis revealed TROP2 overexpression to be an independent prognostic marker for poor DFS in the subgroup of patients with intestinal-type gastric cancer irrespective of lymph node involvement. Conclusion: Results show that TROP2 is an independent prognostic marker for disease recurrence in intestinal type gastric cancer. Due to its wide distribution TROP2 may become an attractive therapeutic target in a subgroup of patients with gastric cancer.